Aluminium toxicity on the activities of antioxidant enzymes in rice (Oryza sativa L.) and chickpea (Cicer arietinum L.) seedlings grown in hydroponic culture (Bangladesh Journal of Botany, 2020)
Effects of four different concentrations of aluminium (10, 50, 100 and 150 μM) on some antioxidant enzyme activities like peroxidase, catalase and superoxide dismutase of the seedlings of rice and chickpea grown in hydroponic culture showed aluminium toxicity which caused a dramatic increase in peroxidase and catalase activities in the root and shoot of rice seedlings. Al (150 μM) caused eight to nine-folds increase in peroxidase and catalase activity, respectively, in the root of rice seedlings. On the contrary, Al stress decreased superoxide dismutase (SOD) activity in the root and shoot of rice seedlings. In chickpea seedlings, Al stress caused a few-folds increases in peroxidase, catalase and SOD activities in the roots and leaves. A dramatic 14.8 and 14.6-folds increase in SOD activity was recorded in the roots and leaves of chickpea seedlings, respectively. It is noted that there is a generic difference between rice and chickpea with respect to the effect of Al stress on SOD activity.